Equine-assisted learning and leadership transformation: an exploratory qualitative study of workplace behavior - Sivagurunathan, Rubentheran; Senathirajah, Abdul Rahman bin S.; Sivagurunathan, Linkesvaran; Arokiasamy, Lawrence; Qazi, Sayeeduzzafar; Haque, Rasheedul; Su, Yanmei (Frontiers in Veterinary Science, 2025)
BackgroundThis study explores how equine-assisted leadership development (EALD) interventions activate experiential processes that reshape leaders’ self-concept, relational schemas, and behaviors. A conceptual model is proposed to explain how non-verbal interaction with horses catalyzes transformational learning.MethodsA qualitative exploratory design was employed to examine leaders’ experiences over 12 months following reintegration into their workplaces. Eight leaders (n = 8) attended a 5-day EALD program, engaging in “join-up” exercises with horses. Data were analyzed through reflexive thematic analysis to identify leadership learning and transformation patterns.FindingsThe reflexive thematic analysis produced three interrelated themes: (1) embodied self-awareness and leadership reflection, (2) transformative learning and behavioral change, and (3) relational leadership and trust-based engagement—which together describe a developmental pathway from immediate embodied feedback to sustained workplace change.Originality/valueThis is the first Malaysian study to show how structured human–animal interaction can elicit sustained leadership shifts. By positioning horses as non-verbal feedback systems, the research highlights embodied, affective, and relational dimensions of leadership development often overlooked in cognitive or skills-based models.